Strategi Digital Marketing Dalam Meningkatkan Penjualan Ikan Hias Cupang (Studi Kasus pada Bastyan Betta Farm Melalui Media Sosial di Desa Dander Kecamatan Pesantren Kota Kediri) - Agustina, Risma Alia; Satriyono, Gandung; Triwidyati, Endang (Jurnal Ilmiah Raflesia Akuntansi, 2024)
In this modern era, the development of information technology has changed the world of marketing in recent years. Traditional and conventional marketing communication methods are now gradually being integrated into the digital world. This type of research uses a descriptive method with a qualitative approach. Qualitative methodology is a research procedure that produces descriptive data in the form of written and spoken words. The presence of digital marketing or advertising has had a positive impact in the business world where the process of marketing a product can easily be done by creating digital photo or video content about a product to be marketed and then uploading it to several available social media application platforms. The conclusion in this research is that the digital marketing strategy carried out by Bastyan Betta Farm to increase sales is by creating and posting interesting photos or videos using social media, namely Instagram, Facebook and Whatsapp.